Straight Jacket: The Implications of Multidimensional Sexuality for Relationship Quality and Stability - Yue Qian; Yang Hu (Sociological Science)
The quality and stability of couple relationships have far-reaching consequences for the well-being of individual partners and patterns of family change. Although much research has compared the quality and stability of same-sex and different-sex relationships, the multidimensional nature of sexuality has received insufficient attention in this scholarship. Individuals in same-sex (different-sex) partnerships do not necessarily identify as gay/lesbian (straight) or report exclusive same-sex (different-sex) attraction—a phenomenon we term "identity/attraction–partnership inconsistency." By analyzing nationally representative longitudinal data collected between 2017 and 2022, we show that identity/attraction–partnership inconsistency is common among U.S. adults, ranging from 2 percent of men in different-sex partnerships to 41 percent of women in same-sex partnerships. Regression results show that such inconsistency is associated with lower relationship quality and higher relationship instability, and these negative ramifications are particularly pronounced among individuals, notably men, in different-sex partnerships. Our findings uncover the implications of multidimensional sexuality for relationship dynamics and outcomes given the rigid institutionalization of different-sex couplehood and the close normative regulation of men's heterosexuality. Our study highlights the importance of incorporating multiple dimensions of sexuality and their interplays into research on couple relationships and family change.